Research on optimization of repeater distribution based on cellular communication system - Shao-hong YAN; Yu-hang WU; Dian-xuan GONG (Tongxin xuebao)
First considering the signal in space link loss,in combination with lowest relay protection field intensity,power and the reasonable analysis and determination of parameters such as system allowance,a repeater Egli model was adopted to cover radius expression was drew.Secondly on the repeater distribution location,center incentive model of cellular communication system was improved to the center-vertex incentive model.The model area of coverage can be increased by 4%,the user coverage increased by 22%.The repeater distribution in communication system provides a good optimization.